Pengaruh Price Discount, Bonus Pack, dan In-Store Display Terhadap Perilaku Impulse Buying Pada Konsumen Willy Mart Luwus - Suryani, Ni Luh Putu Lilis; Dharmayasa, I Putu Arya (Jurnal Pendidikan Ekonomi Undiksha, 2024)
The aim of this research is to determine the effect of price discounts, bonus packs, and in-store displays on impulse buying behavior among Willy Mart Luwus consumers. Determination of the sample of 91 respondents using a nonprobability sampling technique with accidental sampling. The data used is causal quantitative. Using the analysis technique, namely multiple linear regression analysis, classical assumption test, t test, and F test. The results of this study indicate that (1) the price discount has a positive and significant effect on impulse buying for Willy Mart Luwus consumers with a sig. of 0.016; (2) the bonus pack has a positive and significant effect on impulse buying for Willy Mart Luwus consumers with a sig. of 0.015; (3) in-store display has a positive and significant effect on impulse buying for Willy Mart Luwus consumers with a sig. of 0.000; (4) price discounts, bonus packs, and in-store displays have a simultaneous effect on impulse buying (Y) behavior for Willy Mart Luwus consumers with a sig. of 0.000.